Effects of lime and coffee husk compost on growth of coffee seedlings on acidic soil of Haru in Western Ethiopia - Bikila Takala Dibaba; Taye Kufa; Alemayehu Regassa (Brawijaya University, 2020)
A pot experiment was conducted to determine the effects of lime, coffee husk compost and their combinations on growth response of coffee (Coffea arabica L.) seedlings at Haru Research Sub-Center nursery site in West Ethiopia in 2016/17. The experiment was laid out in a factorial experiment arranged in Randomized Complete Block Design with three replications. The treatments included four levels of lime (0, 2, 4 and 6 g/2.5k g soil (pot)) and coffee husk compost (0, 6.25, 12.5 and 18.75 g/2.5 kg soil (pot)). The relevant shoot and root growth parameters data were collected and subjected to Analysis of Variance using SAS package and treatment means were compared at 0.05 probability using Duncan’s Multiple Range Test. The results revealed that lime and coffee husk compost rates significantly (p ≤ 0.01) affected the shoot and root growth of coffee seedlings. The highest growth performance of coffee seedlings (plant height, stem girth, leaf number and area, tap and lateral root length, lateral root number, root volume, stem, leaf and root dry matter) were obtained from the application of 18.75 g/pot coffee husk compost and combined lime and coffee husk compost at the modest levels of 4g/pot lime and 12.5 g/pot coffee husk compost with a non-significant variation. From the study, it can be concluded that application of 18.75 g/pot coffee husk compost or combining 12.5 g/pot of coffee husk compost and 4 g/pot of agricultural lime could be a promising alternative amendment for acid soil management and production of vigorous coffee seedlings in Haru areas. But, further investigations should be continued under field conditions across locations and seasons to evaluate the effects of liming and coffee husk composts in ameliorating soil acidity, and improving growth, yield and quality of coffee varieties and establish their profitable levels for sustainable soil fertility management and production of Wollega coffee in west Ethiopia.